Properties of nano silica modified rubbercrete - Mohammed, B.S. (Elsevier Ltd, 2016)
Inclusion of crumb rubber from scrap tires in concrete as partial replacement to fine aggregate in production of rubbercrete has provided many beneficial impacts to both environments and concrete. Many properties of rubbercrete are improved compared with conventional concrete. However, drawbacks such as reduction in rubbercrete strengths have limited the application of rubbercrete drastically. Therefore, this paper presents a new method on producing rubbercrete with comparable compressive strength to the reference mixture (0 of crumb rubber) by adding nano silica. Twenty four mixtures, with four levels (0, 10, 25 and 50) of crumb rubber replacement to fine aggregate by volume and six levels of nano silica addition (0, 1, 2, 3, 4 and 5), were prepared and tested. The microstructure of these mixtures is also investigated and analyzed. It has been found that the inclusion of nano silica would refine the size of the pores and densify the interfacial transition zone between cement matrix and aggregate in hardened rubbercrete. This has resulted rubbercrete with fair compressive strength compared to conventional concrete. Â© 2016 Elsevier Ltd.